Clinical experience with ferric carboxymaltose in the management of anemia in acute gastrointestinal bleeding - Ballester-Clau, Raquel (Eur J Gastroenterol Hepatol, 2019)
OBJECTIVE: The aim of this study was to assess the efficacy and safety of intravenous ferric carboxymaltose (FCM) following hospitalization for acute gastrointestinal bleeding (AGIB) in the context of a restrictive transfusion strategy. PATIENTS AND METHODS: A retrospective single-center study analyzed patients with AGIB (excluding AGIB secondary to portal hypertension) administered a single FCM dose with or without blood transfusion. RESULTS: Eighty-six episodes in 84 patients were analyzed. Seventy-nine patients had upper AGIB. Nineteen episodes were associated with hemodynamic instability. FCM was administered during hospitalization as a single dose of 1000 mg iron in 84/86 episodes and as a single dose of 500 mg iron in two episodes, with blood transfusion in 60/86 (69.8%) episodes. The mean hemoglobin (Hb) was 9.0 g/dl at admission, 7.6 g/dl at the lowest in-hospital value, 9.4 g/dl at discharge, and 12.7 g/dl at follow-up (mean: 55 days postdischarge) (P<0.001 for follow-up vs. all other timepoints). The lowest mean in-hospital Hb value was 7.2 and 8.8 g/dl, respectively, in patients with transfusion+FCM versus FCM alone; the mean Hb was 12.4 versus 13.7 g/dl at follow-up. In patients administered FCM alone, the mean Hb at follow-up in the subpopulations aged older than or equal to 75 years (n=33), Charlson comorbidity index of at least 3 (n=48), and Hb of up to 10 g/dl at admission (n=47) were 12.6, 13.1, and 13.3 g/dl, respectively. No adverse effects were detected. CONCLUSION: Treatment with FCM for AGIB is associated with a good erythropoietic response and anemia correction after hospitalization, even in severe episodes or when transfusion is needed. FCM is safe and well tolerated, and may support a restrictive transfusion policy.